H5P DIDACTIC TOOLS TO SUPPORT DISTANCE LEARNING IN HIGHER EDUCATION - Mokriiev, Maksym; Kuzminska, OLena (Journal of Information Technologies in Education (ITE), 2021)
The digitalization of education in combination with the student-centered approach, which is based on theories of learning, generations and individualized learning styles, highlights the need to develop interactive didactic tools to support e-learning. On the other hand, the widespread introduction of distance learning in the conditions of quarantine restrictions caused by COVID-19 increases the need to modernize both the resource and organizational and methodological support of the educational process. The materials of this article are devoted to the study of the possibilities of using freely distributed H5P tools to support distance learning in higher education institutions. We analyzed the state of research of the problem of development and implementation of interactive didactic H5P tools in domestic and foreign institutions of higher education; Insufficient use of this tool in domestic universities despite the presence of successful foreign practices has been identified. According to the results of a comparative analysis of the functionality of various means of supporting distance learning, which have become most common in higher education institutions, the benefits of using H5P to maximize the involvement of students in distance learning. The wider possibilities of creation, use and distribution of interactive educational elements on the basis of H5P in comparison with other electronic educational technologies are shown. The results of a survey of NULES of Ukraine teachers on determining the complexity and importance of using different H5P tools to support distance learning are presented. Based on the analysis of teachers' needs, the need for specialized training on pedagogical design of the content of didactic materials H5P, delivery technologies and methods of their use in teaching various disciplines of higher education.